Analysis of Influence of Human Resources Management and Organizational Culture on Employee Performance of PT. Supra Matra Abadi PMKS Aek Nabara - Yoana Yoana; Elida Florentina Sinaga Simanjorang; Mulya Rafika (Quantitative Economics and Management Studies, 2022)
The purpose of this study is to analyze the influence of Human Resource Management and Organizational Culture on employee performance at PT. Supra Matra Abadi PMKS Aek Nabara. The sample in this study were employees of PT. Supra Matra Abadi PMKS Aek Nabara, totaling 89 people. The analysis used is multiple linear regression test and hypothesis testing. The results of the study are partially known, each variable of HR Management and Organizational Culture has a significant effect on the performance of PT. Supra Matra Abadi PMKS Aek Nabara based on n value Sig less than 0.05 and tcount greater than ttable 1,987 . And simultaneously that the variables of Human Resource Management (X1) and Organizational Culture (X2) have an effect on Employee Performance (Y) PT. Supra Matra Abadi PMKS Aek Nabara based on the value of Sig. 0.001 < 0.05 and the calculated F value is 30.511 > from Ftable 3.10. The result of Adjusted R-Square is 0.644 , this means that the contribution of the influence of Human Resource Management and Organizational Culture on the Performance of Employees of PT. Supra Matra Abadi PMKS Aek Nabara is 64.4% and the remaining 35.6% is influenced by other factors in outside of this research.